Ethnography and virtual worlds : a handbook of method / Tom Boellstorff ... [et al.] ; - Boellstorff, Tom; Nardi, Bonnie A.; Pearce, Celia; Taylor, T.L. (Princeton, NJ : Princeton University Press, 2012)
Tom Boellstorff Bonnie Nardi Celia Pearce T. L. Taylor